Electronic cigarettes and oral health: A narrative review - Ismail, Ahmad Faisal; Ghazali, Aini Fatimah (Association of Indian pharmacist-AIP, 2018)
Effects of smoking have been well established and recognized worldwide. With the advancement of technology, ecigarette has gained popularity and became a global trend. However, its safety and how it affects human’s health, especially the oral health is debatable. The aim of this article is to review the potential adverse effect of e-cigarette on oral health. A systematic search was conducted using PubMed/Medline, Web of Knowledge, SCOPUS and EMBASE. The terms used were a combination of "electronic cigarettes", “vape”, “oral health” and “dental”. The search included all studies published dating from 2003 to 2016. Abstracts were analyzed for selection in 2 phases. The first phase selection was based on the title and abstracts alone. The selected abstracts were then included for second phase, where full articles were obtained. The selection was carried out by an independent reviewer. Only 8 articles were included for final analysis in this review. Among 8 articles included, the earliest article was published by Bullen et al. in 2010 and latest by Reuther et al. and Elbal et al. Pilot study was most frequently performed, with only one case report study conducted during the review period. The sample size of the studies ranged from to around 481 of subjects. The evidence presented in our review suggested that e-cigarette use has direct effect on oral health. E-cigarrete also has been used as a tool for smoking cessation, however there is weak evidence on its effectiveness.